A harmonized country‐level dataset to support the global stocktake regarding loss and damage from climate change. (20th January 2022) - Scown, Murray W.; Chaffin, Brian C.; Triyanti, Annisa; Boyd, Emily
Abstract: Under the Paris Agreement, parties should undertake a global stocktake of progress toward meeting the goals of the agreement and tackling climate change. The first global stocktake will be undertaken in 2023, and an assessment of loss and damage from climate change is an important part of the process. Loss and damage refer to the impacts of climate change felt when mitigation and adaptation efforts are inadequate or absent. Much data, including metrics and indicators relevant for loss and damage, are held in existing global databases, but these are disparate and cannot easily be combined and compared to support the global stocktake. We combine relevant primary data sources to provide a harmonized country‐level global dataset containing relevant indicators of recorded losses and damages from climate‐related events; exposure to climate‐related events; country vulnerability and adaptation readiness; scientific studies of climate change attribution; financial support for climate adaptation; and contextual governance conditions. The indicators are standardized against country population and GDP where relevant. We describe original data sources, processing steps, and an overview of key indicators in the dataset. We also compare the assembled data to existing global risk databases; namely, the INFORM risk index and the World Risk Index. This comparison, provided in the Supporting Information, shows a large amount of redundancy among vulnerability and governance indicators, and we suggest that creators of new databases and risk indices be clear about data limitations and the gaps that specific indices attempt to fill in the global data landscape. We recommend the standard use of ISO codes in future databases of this nature, as well as clear metadata regarding how overseas territories are treated relative to their sovereign state, and information on dissolution and creation of states over time. Abstract : We provide a harmonized country‐level dataset to support the Paris Agreement global stocktake, particularly relating to Loss and Damage from climate change. The dataset combines available metrics on recorded losses and damages, exposure to climate‐related hazards, country vulnerability and adaptation readiness, extreme event attribution studies, adaptation financing, and governance factors. These are visualized in maps from low (yellow) to high (brown)—except for human development and governance indicators, which are low (brown) to high (yellow). Note that available records may not represent all losses and damages actually incurred or all adaptation finance flows. The dataset is provided for 267 countries/territories identified by their 3‐digit ISO code, and all indicators are standardized against population or GDP, where relevant, to enable direct comparison among countries.